2017
DOI: 10.1515/amm-2017-0227
|View full text |Cite
|
Sign up to set email alerts
|

Physical Modelling of Tundish Slag Entrainment under Various Technological Conditions

Abstract: This paper deals with the issue of physical modelling of vortexes creation and tundish slag entrainment over the mouth of the nozzle into the individual casting strands. Proper physical model is equivalent to the operational continuous casting machine No. 2 in TŘINECKÉ ŽELEZÁRNY, a.s. Physical modelling methodology and simulated operational conditions are shortly described. Physical modelling was used for the evaluation of current conditions of steel casting at the application of different impact pads in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…The residence time is the overall time of a steel particle "spends" in the tundish or, more technically, the time between entering the tundish via the ladle shroud and leaving it via one of the exit ports (submerged entry nozzles), C-curves are measured in steady state, i.e., with constant water level in the tundish (input flow rate = output flow rate). [8][9][10][11][12] During the measurements it was empirically found that the optimal quantity of tracer in terms of the working range of conductivity probes is 150 ml. In general, three measurements are performed for each set of tundish configurations and casting conditions.…”
Section: Physical Modelmentioning
confidence: 99%
“…The residence time is the overall time of a steel particle "spends" in the tundish or, more technically, the time between entering the tundish via the ladle shroud and leaving it via one of the exit ports (submerged entry nozzles), C-curves are measured in steady state, i.e., with constant water level in the tundish (input flow rate = output flow rate). [8][9][10][11][12] During the measurements it was empirically found that the optimal quantity of tracer in terms of the working range of conductivity probes is 150 ml. In general, three measurements are performed for each set of tundish configurations and casting conditions.…”
Section: Physical Modelmentioning
confidence: 99%
“…The requirements imposed on the used refractory concrete are defined by the operating conditions on the continuous casting machine [1,2]. The operating temperature, usually in the range of 1540-1570 • C, and the exposure time in this environment, often reaching more than 30 hours, are considered essential [3][4][5]. During this time, several thousand tons of liquid metal are cast, which places high demands on the shape stability of the prefab placed in such a working environment Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the reports are concerned with the slag entrainment using physical modeling. Michalek et al developed a physical modeling methodology about the slag entrainment at a critical level of steel, which corresponds to an operational continuous casting machine. The steel level drop process in tundish is similar to that in the ladle to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works showed that researchers used mathematical and physical simulation experiment to study the vortex formation and slag entrainment during ladle teeming, whereas recent works prefer to use water simulation to study the formation of vortex in tundish . The formation of vortex in tundish is inevitable, and it cannot be thoroughly studied only by using physical simulation.…”
Section: Introductionmentioning
confidence: 99%